UV-curable acrylic pressure-sensitive adhesive

A UV-curable acrylic adhesive with reactive functional groups and a cationic photoinitiator addresses the need for low-temperature processing and environmental sustainability, offering high cohesive strength and adhesive performance across various temperatures.

JP2025514273APending Publication Date: 2025-05-02HENKEL KGAA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024563497
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-29
Filing Date
2023-04-24
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

There is a need for UV curable acrylic adhesives that are hot melt processable at low temperatures ranging from room temperature to 120°C and can be cured with 365nm to 405nm UV LED lamps, while also being environmentally friendly and sustainable, and existing technologies do not adequately address these requirements.

Method used

A UV-curable pressure-sensitive adhesive comprising an acrylic polymer with reactive functional groups, a reactive diluent essentially free of mono- or multi-(meth)acrylates, and a cationic photoinitiator, which undergoes rapid cationic crosslinking upon UV irradiation, providing high cohesive strength and high biocontent.

Benefits of technology

The adhesive achieves high cohesive strength and adhesive performance over a wide range of application temperatures, with low process temperatures and environmentally friendly properties, suitable for heat-sensitive substrates and efficient UV curing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025514273000001
    Figure 2025514273000001
  • Figure 2025514273000002
    Figure 2025514273000002
  • Figure 2025514273000003
    Figure 2025514273000003
Patent Text Reader

Abstract

Ultraviolet (UV) curable acrylic pressure sensitive adhesives (PSAs) with high cohesive strength and high biocontent are described. The PSAs have a versatile cure profile and can be cured with traditional mercury bulbs or UV LED lamps, making them particularly useful as high performance tapes. Furthermore, the PSAs are suitable for low temperature processing, especially processing at room temperature to 120°C.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Ultraviolet (UV) curable acrylic pressure sensitive adhesives (PSAs) with high cohesive strength and high biocontent are described. The PSAs have a versatile cure profile and can be cured with traditional mercury bulbs or UV LED lamps, making them particularly useful as high performance tapes. Furthermore, the PSAs are suitable for low temperature processing, especially processing at room temperature to 120°C. [Background technology]

[0002] Pressure sensitive adhesives (PSAs) are aggressive, permanently tacky at room temperature and adhere to surfaces with only light finger pressure. Typically, PSA compositions are applied to various substrates such as paper, fabric, metal, and plastic films, and then converted into many different products, especially pressure sensitive adhesive tapes and labels. These pressure sensitive adhesive products have a wide range of applications in many industries, including the automotive industry for fastening or sealing, the pharmaceutical industry for bandages or transdermal drug delivery systems, the packaging industry for sealing, bonding, or labeling, etc. PSAs can be formulated for application as solution or melt adhesives.

[0003] Hot melt pressure sensitive adhesives (HMPSA) are compositions that combine the properties of hot melt adhesives with those of pressure sensitive adhesives. Hot melt adhesives are solid or semi-solid at room temperature, but melt at elevated temperatures to coat on substrates and return to a solid form on cooling. The combination of these properties results in compositions that melt at elevated temperatures and form a permanently tacky solid coating that cools and adheres to contact. A good workable HMPSA must exhibit high cohesive strength at room temperature, low shrinkage on substrates, retention of pressure sensitive properties during storage and use, and a relatively fluid viscosity at typical coating temperatures (e.g., 80°C to 180°C). Very low molecular weight polymers produce hot melt adhesives with sufficient flow, but the resulting adhesives lack cohesive strength. Very high molecular weight polymers have good cohesive strength, but are too viscous at typical application temperatures to be easily coated on substrates. A high percentage of low molecular weight oil or resin must be blended to reduce the viscosity. The addition of low molecular weight oil or resin reduces cohesive strength and heat resistance. To avoid these problems, polymers of moderate molecular weight have been made with various functional groups that undergo crosslinking reactions by heat or actinic radiation. In this way, sufficient crosslinking can be achieved to increase the adhesion of acrylic PSAs. Acrylic polymers with epoxy functional groups are known in the prior art. Examples of such polymers are described in Patent No. 1186876, but these polymers do not crosslink by UV radiation and / or heat.

[0004] JP 2008-208149 A is directed to an acrylic copolymer having a non-polymerizable oxetane compound and a reactive diluent as a polymerization medium. Polymerization is effected by heat and / or X-ray irradiation to form an adhesive for flat panel displays.

[0005] JP 1994-0816 and JP 1996-060127 describe UV-curable acrylic polymers, but require the addition of multifunctional polyols and other hydroxy functional groups to crosslink the polymer.

[0006] JP 2003-147311 is directed to the use of photopolymerizable diacrylates, which are less desirable for use as adhesives because they are partially crosslinked before application to a substrate.

[0007] U.S. Patent No. 8,796,350 and U.S. Patent No. 9,469,794 describe UV-curable pressure-sensitive adhesives that can be applied at elevated temperatures in the range of 80-180°C, but this may not be suitable for heat-sensitive substrates and / or the adhesive may have a short pot life.

[0008] There is a continuing demand and need in the art for UV curable acrylic adhesives that are hot melt processable at low temperatures ranging from room temperature to 120°C and can be cured with 365nm to 405nm UV LED lamps. Additionally, there is a great demand for more environmentally friendly and sustainable adhesives. The present invention addresses these needs by lowering the processable temperature and increasing the bio-content. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent No. 1186876 [Patent Document 2] JP 2008-208149 A [Patent Document 3] JP 1994-0816 A [Patent Document 4] JP 1996-060127 A [Patent Document 5] JP 2003-147311 A [Patent Document 6] U.S. Patent No. 8,796,350 [Patent Document 7] U.S. Patent No. 9,469,794 Summary of the Invention [Means for solving the problem]

[0010] An ultraviolet (UV) curable acrylic pressure sensitive adhesive (PSA) with high cohesive strength and high biocontent for high performance tapes is described.

[0011] In one embodiment, the UV-curable pressure sensitive adhesive comprises an acrylic polymer prepared from at least one acrylic monomer having a reactive functional group selected from the group consisting of cycloaliphatic epoxides, vinyl ethers, oxiranes, oxetanes, and mixtures thereof; a reactive diluent essentially free of mono- or multi-(meth)acrylates; and a cationic photoinitiator.

[0012] In another embodiment, the UV curable pressure sensitive adhesive comprises: A. 10 to 95 weight percent of an acrylic polymer having at least one terminal or pendant reactive functional group selected from the group consisting of cycloaliphatic epoxides, vinyl ethers, oxiranes, oxetanes, and mixtures thereof; B. 4 to 90% by weight of a reactive diluent essentially free of mono- or multi-(meth)acrylates; and C. 0.01 to 5% by weight of a cationic photoinitiator; The total weight of the UV-curable pressure-sensitive adhesive is 100% by weight.

[0013] In yet another embodiment, the UV curable pressure sensitive adhesive comprises: A. 10 to 95 weight percent of an acrylic polymer having at least one terminal or pendant reactive functional group selected from the group consisting of cycloaliphatic epoxides, vinyl ethers, oxiranes, oxetanes, and mixtures thereof; B. 4 to 90 weight percent of a reactive diluent selected from the group consisting of epoxy-functionalized soybean oil, epoxy-functionalized polybutadiene, epoxy-functionalized polyurethane, epoxy-functionalized polysiloxane, epoxy-functionalized polyisobutylene, epoxy-difunctionalized bisphenol A epoxy resin, epoxy-difunctionalized bisphenol F epoxy resin, epoxy-functionalized polyacrylate, epoxy-functionalized polyethylene glycol, epoxy-functionalized polypropylene glycol, epoxy-functionalized polyether, and mixtures thereof, wherein the reactive diluent is essentially free of mono- or multi-(meth)acrylates; and C. 0.01 to 5 wt. % of a cationic photoinitiator;

[0014] Another embodiment of the invention is directed to an article of manufacture comprising a substrate and a UV-curable pressure sensitive adhesive, the UV-curable pressure sensitive adhesive comprising: A. 10 to 95 weight percent of an acrylic polymer having at least one terminal or pendant reactive functional group selected from the group consisting of cycloaliphatic epoxides, vinyl ethers, oxiranes, oxetanes, and mixtures thereof; B. 4 to 90% by weight of a reactive diluent essentially free of mono- or multi-(meth)acrylates; and C. 0.01 to 5 wt. % of a cationic photoinitiator;

[0015] In another embodiment, the present invention is directed to a UV-curable pressure-sensitive adhesive having a matrix of: (A) an acrylic polymer having reactive terminal or pendant functional groups selected from cycloaliphatic epoxides, vinyl ethers, oxiranes, oxetanes, or mixtures thereof attached to the acrylic polymer backbone; (B) a reactive diluent having terminal or pendant reactive functional groups selected from cycloaliphatic epoxides, oxiranes, oxetanes, vinyl ethers, or mixtures thereof; and (C) a cationic photoinitiator. The matrix is ​​essentially free of mono- or multi-(meth)acrylate groups. The reactive functional groups of the acrylic polymer (A) and the terminal or pendant functional groups of the reactive diluent (B) undergo UV curing to form the pressure-sensitive adhesive in the presence of the cationic photoinitiator (C). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] All documents cited herein are incorporated by reference in their entirety.

[0017] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. In case of conflict, the present specification, including definitions, will control. Preferred methods and materials are described below, although methods and materials similar or equivalent to those described herein can be used in the practice or testing of this disclosure. All publications, patent applications, patents, and other references mentioned herein are incorporated by reference in their entirety. The materials, methods, and examples disclosed herein are for illustrative purposes only and are not intended to be limiting.

[0018] The term "comprising" as used in the specification and claims may include the embodiments "consisting of" and "consisting essentially of." As used herein, the terms "comprising," "including," "having," "can," "containing," and variations thereof are intended to be open-ended transitional phrases, terms, or words that require the presence of the specified components / steps and permit the presence of other components / steps. However, such descriptions should also be construed as describing the composition or method as "consisting of" and "consisting essentially of" the recited components / steps, which permit only the presence of the specified components / steps and impurities that may result therefrom, and exclude other components / steps.

[0019] Numerical values ​​in the specification and claims of this application, particularly when referring to polymers or polymer compositions, reflect average values ​​for compositions that may contain individual polymers of different properties. Moreover, unless otherwise specified, numerical values ​​should be understood to include the same numerical values ​​when converted to the same significant figures, and numerical values ​​that differ from the stated value by less than experimental error of conventional measuring techniques of the type described in this application for determining the value.

[0020] All ranges disclosed herein are inclusive of the recited endpoints and are independently combinable (e.g., the range "from 2 to 10" includes the endpoints 2 and 10, and all intermediate values). The endpoints of the ranges and any values ​​disclosed herein are not limited to the exact ranges or values; they are imprecise enough to encompass values ​​that are close to these ranges and / or values. As used herein, approximation language may be applied to modify quantitative expressions that may vary without resulting in a change in the basic function to which they relate. Thus, values ​​modified by terms such as "about" may not be limited to the exact value specified. In at least some instances, approximation language may correspond to the precision of an instrument for measuring the value. The modifier "about" should also be considered to disclose a range defined by the absolute values ​​of the two endpoints. For example, the phrase "about 2 to about 4" also discloses a range of "2 to 4". The term "about" may refer to plus or minus 10% of the indicated numerical value. For example, "about 10%" may indicate a range of 9% to 11%, and "about 1" may mean 0.9 to 1.1. Other meanings of "about" (such as rounding) will be clear from the context, for example, "about 1" may mean 0.5 to 1.4.

[0021] As used herein, a polymer or oligomer is a macromolecule composed of about 2 or more monomeric units. Polymer and oligomer are used interchangeably in the present invention.

[0022] As used herein, the terms "pressure sensitive adhesive" or "PSA" are used interchangeably and refer to a viscoelastic material that instantly bonds to most substrates upon application of slight pressure and remains permanently tacky.

[0023] As used herein, the term "essentially free" means that the composition contains less than 1% by weight, preferably less than 0.1% by weight, and most preferably more than trace amounts of the specified component.

[0024] As used herein, the term "no additional ingredients added" means that the specified ingredient has not been intentionally added, although trace amounts may be present.

[0025] The present invention relates to an ultraviolet (UV) curable pressure sensitive adhesive comprising: (A) an acrylic polymer having cationically reactive terminal or pendant functional groups attached to the acrylic polymer backbone; (B) a reactive diluent having terminal or pendant functional groups selected from cycloaliphatic epoxides, oxiranes, oxetanes, vinyl ethers, or mixtures thereof; and (C) a cationic photoinitiator. The acrylic polymer having cationically reactive terminal or pendant functional groups attached to the acrylic polymer backbone (A) and the terminal or pendant functional groups of the reactive diluent (B) undergo a rapid cationic crosslinking reaction catalyzed by superacid generated by decomposition of the cationic photoinitiator upon UV irradiation. The initial rapid crosslinking provides green strength to the adhesive, while the post-UV crosslinking, which lasts from minutes up to days, provides high cohesive strength and high adhesive performance over a wide range of application temperatures.

[0026] Acrylic polymers are: (i) a first monomer having a reactive functional group selected from a cycloaliphatic epoxide, a vinyl ether, an oxirane, an oxetane, or a mixture thereof; and (ii) Acrylic monomers consisting of acrylic or methacrylic acid derivatives of formula CH2=CH(R1)(COOR2) (Wherein, R1 is H or CH3, and R2 is C 1-24 alkyl chains); It is prepared from The amount of the first monomer (i) is about 0.001 to about 10 g per 100 g of the acrylic polymer. In a more preferred embodiment, the amount of the first monomer (i) is about 0.01 to about 5 g per 100 g of the acrylic polymer.

[0027] Suitable first monomers (i) of the polymer include vinyl or acrylic compounds that are capable of undergoing a UV-activated cationic crosslinking reaction and imparting green strength to the adhesive and contain a cationic UV-reactive functional group having the formula (1):

[0028] [ka]

[0029] In the formula, R 1 is O, S, C=O, or a linear, branched or cyclic alkylene, oxyalkylene, or arylene; R 2 R is a linear, branched and cyclic alkyl or alkoxy, aryl, H, halogen, C=O, or a covalently fused alicyclic ring. 1 is part of R 3 (CH2) n where n is 0 to 3; X is an acrylate, methacrylate or contains a -WY group; W is O, S, amide, carbonate, urethane, urea, siloxane, or combinations thereof; Y is -R 4 -C(R 5 )=CH2, where R 4 is a linear or branched chain C 2-10 Alkylene or C 2-10 oxyalkylene or arylene or a derivative thereof, R 5 is H or CH3.

[0030] One suitable first monomer (i) is represented by structural formula (1A):

[0031] [ka]

[0032] In the formula, R 1 is H or CH3.

[0033] Preferred vinyl or acrylic compounds for use as the first monomer (i) are represented by structural formula (1B):

[0034] [ka]

[0035] In the formula, R 2 is H or CH3.

[0036] Another preferred vinyl or acrylic compound for use as the first monomer (i) is represented by structural formula (1C):

[0037] [ka]

[0038] Another preferred vinyl or acrylic compound for use as the first monomer (i) is represented by structural formula (1D).

[0039] [ka]

[0040] Yet another preferred vinyl or acrylic compound for use as the first monomer (i) is represented by structural formula (1E):

[0041] [ka]

[0042] Yet another preferred vinyl or acrylic compound for use as the first monomer (i) is represented by structural formula (1F).

[0043] [ka]

[0044] Yet another preferred vinyl or acrylic compound for use as the first monomer (i) is represented by structural formula (1G).

[0045] [ka]

[0046] Yet another preferred vinyl or acrylic compound for use as the first monomer (i) is represented by structural formula (1H).

[0047] [ka] In the formula, R 6 is H or CH3.

[0048] Yet another preferred vinyl or acrylic compound for use as the first monomer (i) is represented by structural formula (1I):

[0049] [ka]

[0050] In the formula, R is H or CH3.

[0051] In another embodiment, the first monomer (i) is a vinyl or acrylic compound that can undergo either a fast UV-activated cationic crosslinking reaction or a slow UV post-crosslinking reaction, thus providing the adhesive with high performance adhesive strength. These exemplary monomers include glycidyl methacrylate (GMA), 4-hydroxybutyl acrylate glycidyl ether (4-HBAGE), cycloaliphatic epoxide monomers M100 and A400 (Daicel), OXE-10 (Kowa), UVIVURE S105 and S170, CD535 (Sartomer), 4-vinyl-1-cyclohexane-1,2-epoxide (Dow). Another example of a suitable reactive functional group has the following formula (2A):

[0052] [ka]

[0053] The acrylic monomer (ii) consists of one monomer or mixture of monomers from acrylic or methacrylic acid derivatives of formula CH2=CH(R1)(COOR2), where R1 is H or CH3 and R2 is C1-24 alkyl. The acrylic monomer (ii) includes branched (meth)acrylic isomers such as methyl acrylate, ethyl acrylate, ethyl methacrylate, methyl methacrylate, n-butyl acrylate, n-butyl methacrylate, n-pentyl acrylate, n-hexyl acrylate, n-heptyl acrylate, and n-octyl acrylate, n-nonyl acrylate, lauryl methacrylate, cyclohexyl acrylate, i-butyl acrylate, i-butyl methacrylate, n-butyl methacrylate, 2-ethylhexyl acrylate, stearyl methacrylate, and isooctyl acrylate, or mixtures thereof. Exemplary acrylic monomers (ii) are monofunctional acrylates and do not include diacrylate or multiacrylate monomers.

[0054] The selection and relative amounts of the specific acrylic and vinyl monomers that make up the acrylic polymer used to prepare the adhesive of the present invention will depend on the desired final properties and intended end use of the adhesive. The selection of the acrylic and vinyl monomers and their relative amounts in the final composition to achieve the desired properties is within the expertise of one skilled in the art.

[0055] In UV-curable pressure-sensitive adhesives, the acrylic polymer has a Tg value of less than 0° C. and a weight average molecular weight (Mw) of about 1,000 to about 3,000,000 g / mol. To achieve high cohesive strength and high performance of the UV-curable adhesive, a higher molecular weight acrylic polymer is desirable. The weight average molecular weight (Mw) of the acrylic polymer is preferably about 50,000 to about 2,000,000 g / mol, and even more preferably about 200,000 to about 1,000,000 g / mol. For UV-curable pressure-sensitive adhesives that can be applied at room temperature, the preferred weight average molecular weight (Mw) of the acrylic polymer is about 5,000 to about 500,000 g / mol, and even more preferably about 10,000 to about 100,000 g / mol.

[0056] In the polymerization process, the first monomer (i) and the acrylic monomer (ii) are converted by radical polymerization into an acrylic polymer. In the polymerization, the monomers are selected so that the resulting polymer has pressure-sensitive adhesive properties so that it can be used to prepare adhesives, in particular according to Donatas Satas, Handbook of Pressure-Sensitive Adhesives (Van Nostrand, NY, 1989). For these applications, it is advantageous for the glass transition temperature of the resulting polymer to be less than about 0°C.

[0057] The acrylic polymer is essentially free of multi(meth)acrylate, polyol or OH functionality and the polymer remains essentially linear after polymerization.

[0058] The reactive diluent of the UV-curable pressure-sensitive adhesive is a polymer, oligomer or macromer containing at least one terminal or pendant functional group selected from cycloaliphatic epoxides, oxiranes, oxetanes, vinyl ethers, or mixtures thereof. The reactive diluent is essentially free of mono- or multi-(meth)acrylates. The reactive diluent has a weight average molecular weight of about 100 to about 500,000 g / mol. Furthermore, the reactive diluent is preferably epoxy-functionalized soybean oil, epoxy-functionalized polybutadiene, epoxy-functionalized polyurethane, epoxy-functionalized polysiloxane, epoxy-functionalized polybutadiene, epoxy-functionalized polyisobutylene, epoxy-difunctionalized bisphenol A epoxy resin, epoxy-difunctionalized bisphenol F epoxy resin, epoxy-functionalized polyacrylate, epoxy-functionalized polyethylene glycol, epoxy-functionalized polypropylene glycol, epoxy-functionalized polyether, or mixtures thereof.

[0059] In a preferred embodiment, the reactive diluent is bio-derived or made from a bio-source. Bio-derived or bio-sourced reactive diluents can be produced by the reaction of renewable precursors such as vegetable oils, sugars, tannins, cardanol, terpenes, rosin, and lignin. The reactive diluent can range from about 4 to about 90% by weight based on the total weight of the acrylic polymer. One of the main functions of the diluent is to reduce and control the viscosity of the adhesive, thereby allowing it to be coated at low temperatures. Low adhesive viscosity and low coating temperatures are always preferred for the thermal stability of the adhesive, heat-sensitive substrates, LED curing, and energy consumption of the coating process. However, non-reactive diluents typically compromise the cohesive strength of the adhesive. To achieve high cohesive strength and high performance of UV-curable adhesives, higher molecular weight and high viscosity acrylic polymers are usually used. The reactive diluent in the composition reduces the viscosity to about 1,000 to about 90,000 cps, which is in the range of being applicable at 25 to 120°C, and more importantly, does not degrade the cohesive strength of the adhesive after UV curing. The reactive diluent participates in cationic crosslinking reactions, increasing the crosslink density and cohesive strength of the adhesive. However, the reactive diluent must balance a controlled amount of epoxy functionality between the acrylic polymer and the reactive diluent to avoid excessive crosslinking that would produce an adhesive film with poor release, poor adhesion, and poor wettability. The reactive diluent can be a polymer, oligomer, or macromer containing at least one terminal or pendant functional group selected from cycloaliphatic epoxides, oxiranes, oxetanes, vinyl ethers, or mixtures thereof. The preferred reactive diluent has a weight average molecular weight of about 100 to about 100,000 g / mol. The reactive diluent is preferably an epoxy-functionalized polybutadiene, an epoxy-functionalized polyurethane, an epoxy-functionalized polysiloxane, an epoxy-functionalized polyisobutylene, an epoxy-difunctionalized bisphenol A epoxy resin, an epoxy-difunctionalized bisphenol F epoxy resin, an epoxy-functionalized polyacrylate, an epoxy-functionalized polyethylene glycol, an epoxy-functionalized polypropylene glycol, an epoxy-functionalized polyether, or a mixture thereof.Examples of commercially available reactive diluents include Ceroxide 2021P, Ceroxide 8000, Ceroxide 2081, EHPE3150, Epolead GT401, Epolead PB series, Epofriend series, Uniqure S128, Uniqure S150, Uniqure S160, EPON828, EPON862, KF-8100, KF-8145, KF-12102, KEW-L2000, KET-L3000, and DER 330. The reactive diluent can range from about 4 to about 90% by weight, based on the total weight of the UV-curable adhesive.

[0060] A particular embodiment of the reactive diluent is bio-derived or made from a bio-source. Bio-derived or bio-sourced reactive diluents can be produced by the reaction of renewable precursors such as vegetable oils, sugars, tannins, cardanol, terpenes, rosin, and lignin. Examples of bio-derived reactive diluents include Vicoflex-7170 and epoxidized soybean oil NatureflexX ESO. These diluents are compatible with the acrylic polymers of the present invention and also slow down the post-UV cure process to prolong the shadow cure and improve the wetting of the adhesive to the substrate. This improved wetting and adhesion results in improved bond strength over a wide range of application temperatures, with SAFT values ​​up to 200°C.

[0061] The matrix of the UV-curable pressure sensitive adhesive comprises (A) an acrylic polymer having reactive terminal or pendant functional groups attached to the acrylic polymer backbone selected from cycloaliphatic epoxides, vinyl ethers, oxiranes, oxetanes, or mixtures thereof, and (B) a reactive diluent having terminal or pendant reactive functional groups selected from cycloaliphatic epoxides, oxiranes, oxetanes, vinyl ethers, or mixtures thereof. The reactive functional groups on both the polymer and the reactive diluent undergo a UV crosslinking reaction in the presence of a cationic photoinitiator (C) to form a crosslinked network with high cohesive strength over a wide range of application temperatures.

[0062] The UV-curable pressure-sensitive adhesive further comprises a cationic photoinitiator. The main function of the cationic photoinitiator is to initiate the crosslinking reaction between the acrylic polymer (A) and the reactive diluent (B) when irradiated with UV light. The mechanism of the cationic photoinitiator is to form an excited state when irradiated with UV light, which then collapses to release a cationic radical. This cationic radical reacts with a solvent, moisture, or other hydrogen atom donor to generate a protonic acid, which is an active species that initiates the crosslinking reaction between the acrylic polymer (A) and the reactive diluent (B). A radical-reactive functional group such as (meth)acrylic C=C reacts with the cationic radical decomposed from the cationic photoinitiator by UV irradiation. Such a reaction prevents the formation of a superacid. Preferably, the adhesive composition of the present invention is essentially free of radical-reactive functional groups such as mono- or multi-(meth)acrylates to avoid competition and interference between radical and cationic curing during UV irradiation.

[0063] Many cationic photoinitiators, including iodonium salts and sulfonium salts, can be used to crosslink the acrylic polymer (A) with the reactive diluent (B) of the present invention. These include, for example, diaryliodonium salts, triarylsulfonium salts, dialkylphenylsulfonium salts, dialkyl(hydroxydialkylphenyl)sulfonium salts, and ferrocenium salts. The anions of these salts are generally less nucleophilic, and are typically SbF6-, PF6-, AsF6-, BF4-, B(C6F5)4- or Ga(C6F5)4-, PF n (Rf) 6-n -. Specific examples include Omnicat 320, Speedcure 937, Speedcure 938, Speedcure 939, CPI-310B, CPI-200K, CPI-210S, and IK-1. Particularly useful cationic photoinitiators are the soluble, LED-reactive sulfonium salt photoinitiators having structural formulas (6A) and (7A).

[0064] [ka]

[0065] In the formula, R is C3H7, C 12 H 25 and W is S, SO, SO2 or CO.

[0066] [ka]

[0067] In the formula, R 1 and R 2 are independently H, CH3, C2H5, C3H7, and C 12 H 25 , OCH3, OC2H5, OC3H7 or OC 12 H 25 It is.

[0068] These cationic photoinitiators have good solubility in the UV-curable pressure-sensitive adhesives of the present invention, promote efficient thick film UV cure, exhibit thermal stability prior to cure, exhibit increased cure speed, and reduce dark cure times.

[0069] In a further embodiment, the cationic photoinitiator of the UV-curable pressure sensitive adhesive has the following structure:

[0070] [ka]

[0071] In the formula, R is C3H7, C 12 H 25 and W is S, SO, SO2 or CO.

[0072] In one embodiment, the UV curable pressure sensitive adhesive comprises: A. 10 to 95 weight percent of an acrylic polymer having at least one terminal or pendant reactive functional group selected from the group consisting of cycloaliphatic epoxides, vinyl ethers, oxiranes, oxetanes, and mixtures thereof; B. 4 to 90% by weight of a reactive diluent essentially free of mono- or multi-(meth)acrylates; and C. 0.01 to 5% by weight of a cationic photoinitiator; The total weight of the UV-curable pressure-sensitive adhesive is 100% by weight.

[0073] The UV-curable pressure sensitive adhesive optionally further comprises a tackifier, a plasticizer, a heat stabilizer, an antioxidant, a desiccant, and / or a solvent.

[0074] UV-curable pressure-sensitive adhesives, optionally containing about 10-50% of the adhesive, include tackifiers, which are conventionally used in the manufacture of PSAs. Reference may be made expressly to Donatas and Satas, Handbook of Pressure-Sensitive Adhesive Technology (Van Nostrand, NY, 1989), or to a depiction of the state of the art in any PSA-related literature. In general, any natural resin compatible with the corresponding acrylic polymer may be used. Reference may be made in particular to all natural resins. Non-limiting examples include pinene resins, indene resins, rosins, terpene resins, terpene phenolic resins, gum rosins, wood rosins, tall oil rosins, distilled rosins, hydrogenated rosins, dimerized rosins, polymerized rosins, and their disproportionated and esterified derivatives and salts.

[0075] Other suitable tackifiers include aliphatic and aromatic hydrocarbon resins, hydrogenated hydrocarbon resins, and functionalized hydrocarbon resins. Non-limiting examples include aliphatic and aromatic hydrocarbon resins, C5 resins, C9 resins, and other hydrocarbon resins. Any desired combination of these resins may be used to adjust the properties of the resulting PSA according to the desired final properties.

[0076] Specific examples of these tackifiers include Techross R86, Silverite RE85GB, Foral 85-E, Wingtack 95, Cleartack W85, etc. A preferred embodiment of the tackifier is a liquid tackifier that may further reduce the viscosity of the adhesive. Examples include polymerized C5 petroleum feedstreams and polyterpenes such as Wingtack 10, and Escorez 2520, liquid rosin ester tackifier Silverite 2038, etc.

[0077] UV curable pressure sensitive adhesives may optionally contain heat stabilizers or antioxidants. Among the applicable stabilizers or antioxidants utilized herein are high molecular weight hindered phenols and multifunctional phenols, such as sulfur and phosphorus-containing phenols. Hindered phenols are well known to those skilled in the art and may be characterized as phenolic compounds that also contain sterically bulky radicals in close proximity to the phenolic hydroxyl group. Any known heat stabilizer is suitable, and preferred classes of heat stabilizers include, but are not limited to, phenolic antioxidants, alkylated monophenols, alkylthiomethylphenols, hydroquinones, alkylated hydroquinones, tocopherols, hydroxylated thiodiphenyl ethers, alkylidene bisphenols, O-, N-, and S-benzyl compounds, hydroxybenzylated malonates, aromatic hydroxybenzyl compounds, triazine compounds, amine antioxidants, arylamines, diarylamines, polyarylamines, acylaminophenols, oxamides, metal deactivators, phosphites, phosphonites, benzylphosphonates, ascorbic acid (vitamin C), hydroxylamines, nitrones, thiosynergists, benzofuranones, indolinones, and mixtures thereof. Examples of commercially available stabilizers include Irganox 1010, Irganox 1520 / 1726, Irganox 565, Irganox 3114, Irgastab FS301, Tinuvin 123, Tinuvin 292, Tinuvin 5100, Tinuvin 249, Tinuvin 770, BHT, 4-MEHQ. The use of heat stabilizers is optional, but in some cases is not preferred. If a heat stabilizer is used, it may be present at a level of about 0.001 g to about 0.5 g by weight, based on 100 g total weight of the adhesive.

[0078] In further embodiments, desiccants may be used to improve the moisture barrier properties of the adhesive. Fillers with suitable desiccant properties for use are referred to as desiccant fillers and may be any that provide suitable moisture capture rate, capacity, and residual moisture level (the minimum moisture level at which the desiccant can actively remove moisture) to meet the moisture tolerance level of a particular electronic device. Desiccant fillers are capable of reacting with, absorbing, or adsorbing water and / or water vapor. A representative list of such desiccants is found in Dean, J. Lange, "Handbook of Chemistry," McGraw-Hill, Inc., New York, NY, 1999, p. 11.5. When used as a moisture scavenger, the desiccant may be present at a level of about 0.001% to about 0.5% by weight based on the total weight of the adhesive.

[0079] The adhesive may also contain a variety of other additives, such as plasticizers and fillers, all of which are conventionally used in the manufacture of PSAs. Any desired combination of these or other additives may be used to adjust properties such as the viscosity and rheology of the resulting adhesive according to the final properties desired.

[0080] In a further advantageous development, one or more plasticizers or non-reactive diluents, such as low molecular weight acrylic polymers, phthalates, whale oil plasticizers, mineral oils, plasticizer resins, etc., are added to the UV-curable pressure-sensitive adhesive to adjust the viscosity and rheology of the adhesive before and after curing.

[0081] The UV-curable pressure-sensitive adhesive of the present invention is mostly 100% solid and is either in the form of a hot melt, warm melt or room temperature liquid. It has a Brookfield viscosity at the coating temperature, typically in the range of about 1,000 to about 900,000 cps at about 25 to about 150°C, preferably 1,000 to 90,000 cps at about 25 to about 120°C. Such a viscosity range allows the adhesive to be coated into a film. The thickness of the film is in the range of about 25 to about 250 μm, preferably about 50 to about 150 μm.

[0082] As known to those skilled in the art, the preparation of the acrylic polymer can be carried out by solution, emulsion, or bulk polymerization procedures using well-known free radical polymerization techniques. The polymer and uncured adhesive can then be formed into a neat adhesive by removal of the solvent, coagulation of the latex, or melt processing of the neat polymer.

[0083] The polymerization may be carried out in the presence of one or more organic solvents and / or in the presence of water. Suitable organic solvents or mixtures of solvents are alkanes such as hexane, heptane, octane, isooctane, and cyclohexane; aromatic hydrocarbons such as benzene, toluene, and xylene; esters such as ethyl acetate, propyl acetate, butyl acetate, and heptyl acetate; halogenated hydrocarbons such as chlorobenzene; alkanols such as methanol, ethanol, isopropanol, ethylene glycol, and ethylene glycol monomethyl ether; ethers such as diethyl ether and dibutyl ether; ketones such as acetone, methyl ethyl ketone; or mixtures thereof.

[0084] In one embodiment of this method, the polymerization reaction proceeds in the presence of the free radical initiator AIBN in an ethyl acetate solvent.

[0085] In another embodiment of this method, the polymerization reaction proceeds in a binary solvent system of ethyl acetate and isopropanol in the presence of the free radical initiator AIBN.

[0086] The acrylic polymers prepared for the UV-curable pressure-sensitive adhesives of the present invention generally have an average molecular weight (Mw) of 1,000 to 3,000,000 g / mol, preferably 5,000 to 500,000 g / mol, as measured by gel permeation chromatography (GPC) or matrix-assisted laser desorption / ionization mass spectrometry (MALDI-MS).

[0087] The UV-curable pressure-sensitive adhesive can be formulated to be a solvent-based or water-based adhesive and can be used to make an adhesive film and then remove the solvent or water by drying the film. For use as the UV-curable pressure-sensitive adhesive of the present invention, the acrylic polymer is essentially solvent-free. The solvent can be removed before or after curing, preferably in a reaction tank or vacuum mixer. The solvent used to make the acrylic polymer and form the UV-curable adhesive is removed in a reaction tank or vacuum mixer before coating. However, the UV-curable pressure-sensitive adhesive can also be formulated to be a solvent-based or water-based adhesive and can be used to make an adhesive film and then remove the solvent or water by drying the adhesive film.

[0088] The adhesive composition of the present invention is essentially free of radically reactive functional groups to avoid competition and interference between radical and cationic curing during UV irradiation. Radical reactive functional groups, such as (meth)acrylic C=C, can react with cationic radical fragments decomposed from cationic photoinitiators upon UV irradiation and prevent the formation of superacids. Such radically curable components are, for example, mono- or multi-(meth)acrylates.

[0089] Yet another embodiment relates to an article manufactured using the adhesive of the present invention. The adhesive is in the form of a film, such as a tape, label, coating, etc. Application of the UV-curable pressure-sensitive adhesive can be accomplished using any conventional means, such as roller, slot orifice, spray, or extrusion coating. Non-limiting examples of substrates include films, tapes, sheets, panels, foams, etc.; they can be made of materials such as paper, fabric, metal foil, glass, plastic (polyester, PE, PP, BOPP, and PVC), non-woven fibers, metal, foil, glass, natural rubber, synthetic rubber, wood, plywood, or cement. When the coated substrate is used in the form of a self-winding roll, the back side of the substrate is typically coated with a release coating to prevent the adhesive from adhering to the back side of the substrate. When the substrate is applied to both sides and rolled, a peelable paper or other protective means is placed over the adhesive on one side to prevent the adhesive from adhering to the adhesive on the other side. In some applications, a second substrate may be applied directly to the adhesive.

[0090] In many articles with pressure sensitive adhesives, the adhesive is applied to a backing or substrate prior to crosslinking. Adhesives are typically formulated to have sufficient viscosity for application at temperatures ranging from 25 to 180°C.

[0091] The pure PSA of the present invention has a melt viscosity of 1,000 to 90,000 cPs at low application temperatures of about 25 to about 120° C. The presence of the reactive diluent reduces the viscosity of the instant UV-cure adhesive, allowing for low application temperatures ranging from room temperature to about 120° C. The low application temperatures are particularly preferred for heat sensitive substrates, including electronic boards.

[0092] Pressure-sensitive adhesive films can be formed by applying the adhesive as is to a release liner such as silicone-coated paper or plastic film followed by UV light irradiation, and the adhesive can be removed from the release liner and used as a free film for lamination and transfer to a target substrate. The UV-curable pressure-sensitive adhesives of the present invention can be crosslinked in air by irradiation with UV light in the range of 200-500 nm, preferably 280-400 nm, depending on the cationic photoinitiator in the adhesive composition. Irradiation can be immediate, or preferably while the adhesive film is being freshly coated. A nitrogen blanket can also be used during the coating and curing process to exclude moisture.

[0093] The adhesive composition is irradiated with UV light for a time sufficient to transform the low cohesive composition into a viscoelastic adhesive with a higher modulus. The exact length of UV exposure or dose depends on the nature and intensity of the UV light, the amount of cationic photoinitiator, the acrylic polymer and adhesive composition, the thickness of the adhesive film, environmental factors such as relative humidity and temperature, and the distance between the radiation source and the adhesive film. The dose or length of UV exposure is controlled by the line speed. To reduce the heat load on heat-sensitive substrates, it may be appropriate to match the lamp power to the line speed or to partially shield the line belt.

[0094] Actinic light from any source may be used with the adhesive as long as the source provides an effective amount of ultraviolet light. Suitable UV sources are carbon arcs, mercury vapor arcs, fluorescent lamps with special ultraviolet emitting phosphors, electronic flash lamps, etc., lasers of specific wavelengths, UV LEDs, or combinations thereof. Preferred lamps are electrodeless microwave-driven lamps from Fusion Systems, Inc., or commercially conventional high or medium pressure mercury lamps, for example, with an output of 80-240 W / cm. Particularly preferred UV lights are high intensity LEDs with wavelengths of 365 nm, 385 nm, 395 nm, 405 nm, or combinations thereof. The adhesive composition of the present invention generally exhibits maximum sensitivity to wavelengths in the ultraviolet range of 280-400 nm.

[0095] The adhesive of the present invention may be used to bond a first substrate to a second substrate. Substrates include, but are not limited to, paper, plastic, glass or plastic-coated glass, wood, cement, metal, foil, and the like. The adhesive may be applied by a variety of methods, including coating or spraying a sufficient amount to bond the substrates together. The adhesive-coated substrate may be irradiated before or after bonding. Although the crosslinking reaction begins immediately after UV irradiation, it may not be completed for several days, so there is a time period between immediately after irradiation and gelation for bonding to occur. In some cases, bonding is performed before UV irradiation to obtain optimal wet-out and adhesion.

[0096] The pressure sensitive adhesive of the present invention may be advantageously used in the manufacture of adhesive articles, including but not limited to industrial tapes and transfer films. Single-sided and double-sided tapes, as well as supported and unsupported free films, are encompassed by the present invention. In one embodiment, the adhesive article comprises an adhesive coated on at least one major surface of a backing having a first and second major surface. Useful backing substrates include, but are not limited to, foam, metal, paper, fabric, and various polymers such as polypropylene, polyamide, polyester, polyethylene terephthalate, and mixtures thereof. The adhesive may be present on one or both sides of the backing. When the adhesive is coated on both sides of the backing, the adhesive coatings can be the same or different.

[0097] The following examples are provided to further illustrate the present invention, but are intended to illustrate, not limit, the present invention and are intended to be illustrative of, and not limiting of, the present invention. EXAMPLES

[0098] The adhesives and their properties were tested according to the test procedures or methods described below.

[0099] viscosity: A Brookfield DV-1 viscometer was used to measure the viscosity. The tests used 11 g samples with spindle number 27 at temperatures ranging from 25 to 120°C and speed settings ranging from 1 to 4 rpm.

[0100] Preparation of adhesive coating: Adhesive coatings were made using a benchtop Chemsultant® hot melt laminator coater. The adhesive was heated to 100-135°C and coated onto a 2 mil (51 μm) thick silicone coated PET release liner. The adhesive on the PET liner was irradiated at a specific line speed until the required UV dose was reached. The UV light source was either an H-bulb (Fusion Systems) or a Heraeus 365 nm LED lamp. The film was then laminated and transferred to a polyethylene terephthalate substrate (Mylar®, DuPont) and conditioned at 23°C and 50% relative humidity.

[0101] UV Dose: The UV dose was measured and recorded using an EIT Powerpack II.

[0102] Shear Adhesion: Shear adhesion was measured according to Procedure A, PSTC-107, adapted as follows. All test specimens of acrylic polymers were UV irradiated according to the procedure above. After the test panels were wet for 15 minutes, a 1 kg shear load was applied to a ½ inch by 1 inch area to measure shear adhesion. All tests were performed at 23°C and 50% relative humidity. The time to failure was recorded.

[0103] Loop Tuck: Loop tack was measured according to Test Method B, PSTC-16, adapted as follows. A Loop Tack Tester was used for the measurements. All acrylic polymer test specimens were UV irradiated according to the procedure above. The adhesive was coated onto a 2 mil PET film backing and the test specimen size was 6 inches by 1 inch.

[0104] Peel Adhesion: Peel adhesion at 180° between the substrate and adherend was measured according to Test Method A, PSTC-101, adapted as follows. All test samples of acrylic polymers were UV irradiated according to the procedure above. Peel strength was measured after the stainless steel panel was wetted for 15 minutes.

[0105] Shear Adhesion Failure Temperature (SAFT): Three specimens measuring 1" x 3" were cut from each cured specimen in the machine coating direction. SAFT panels (mirror steel) were cleaned with ethyl acetate. The specimens were applied to the steel panel, overlapping up to the engraved line so that a 1" x 1" square of adhesive was in contact with the test panel. A straight blade wooden applicator was used to scrape the test area to ensure good contact between the panel and the test specimen. The specimens were placed in a test oven at room temperature. A heating program was started and a 1 kg shear load was applied when the temperature reached 40°C. The oven temperature was increased at 0.5°C / min to 200°C and the failure temperature (SAFT) was recorded.

[0106] Example 1 A four-necked, 1 L round-bottom polymerization flask was equipped with a thermometer connected to a temperature controller, a condenser, an overhead mechanical stirrer, two addition funnels, and a nitrogen inlet / outlet. The setup was purged with nitrogen gas for 15 minutes. The following mixture of monomers was prepared: 2-ethylhexyl acrylate (78.0 g), methyl acrylate (71.6 g), 1-acrylomethyl-3,4-cyclohexene epoxide (0.5 g). One of the funnels was charged with 100 g of the monomer mixture. Another funnel was charged with the initiator 2,2'-azobis-(2-methylpropionitrile) (AIBN, 0.6 g) and ethyl acetate (40 mL). The polymerization flask was charged with the remaining monomer mixture (50 g), the initiator AIBN (0.2 g), and ethyl acetate (80 mL). The mixture was heated to vigorous reflux and held for 15 minutes. The monomer mixture in the funnel was then added continuously at a constant rate over a period of 2 hours. At the same time, the initiator solution in the funnel was added continuously at a constant rate over a period of 3 hours. Once the addition of the initiator solution was complete, the mixture was stirred at reflux for an additional 2 hours. A short half-life initiator (0.75 g) and ethyl acetate (20 mL) were placed in the initiator funnel and then added to the polymerization flask over a period of 1 hour to reduce residual monomer. An acrylic polymer was obtained with a weight average molecular weight Mw of 277,000 g / mol by GPC and a PDI of 6.1. The polymerization solution was cooled to 60°C. Techcross R86 tackifier (21.4 g) and cationic photoinitiator OmniCat 320 (1.0 g) were added and mixed thoroughly for 15 minutes. After the ethyl acetate was removed under vacuum at 60°C, a UV-curable pressure-sensitive adhesive with a viscosity of 100,000 cps (Brookfield) at 135°C was obtained. Viscosity increased by 20% in 24 hours at 135°C. As a result, the film coating had high viscosity and was not thermally stable above 135°C.

[0107] Example 2 The reactive diluent epoxidized soybean oil Natureflex X ESO was added to formulate a UV-curable pressure sensitive adhesive of Example 1. The resulting PSA properties are shown in Table 1. The resulting adhesive was coated onto 2 mil PET film at a low temperature of 110-120°C to a thickness of 2 mil and irradiated with 60 mJ / cm using a Fusion H bulb.2 The adhesive was cured with a UVC dose of 1000 nm. The PSA properties were tested on stainless steel panels according to the PSTC methods for peel, loop tack, shear, and SAFT. With the addition of epoxidized soybean oil, the UV-cured pressure-sensitive adhesive exhibited a much lower, coatable viscosity and less viscosity change over time at low temperatures, improving the thermal stability for hot melt coating processes. Furthermore, the addition of epoxidized soybean oil improved the overall PSA properties, especially the cohesive strength and high temperature adhesive strength.

[0108] [Table 1]

[0109] Example 3 A four-necked, 1 L round-bottom polymerization flask was equipped with a thermometer connected to a temperature controller, a condenser, an overhead mechanical stirrer, two addition funnels, and a nitrogen inlet / outlet. The setup was purged with nitrogen gas for 15 minutes. A mixture of the following monomers was prepared: butyl acrylate (148.8 g), and 1-acrylomethyl-3,4-cyclohexene epoxide (1.2 g). One of the funnels was charged with 112 g of the monomer mixture. Another funnel was charged with initiator 2,2'-azobis-(2-methylpropionitrile) (AIBN, 0.1 g), isopropanol (15 g), and ethyl acetate (45 mL). The polymerization flask was charged with the remaining monomer mixture (38 g), initiator AIBN (0.2 g), isopropanol (6 mL), and ethyl acetate (34 mL). The mixture was heated to vigorous reflux and held for 15 minutes. The monomer mixture in the funnel was then added continuously at a constant rate for 2 hours. Simultaneously, the initiator solution in the funnel was added continuously at a constant rate for 3 hours. Once the initiator solution addition was complete, the mixture was stirred at reflux for an additional 2 hours. A short half-life initiator (0.75 g) and ethyl acetate (25 mL) were charged to the initiator funnel and then added to the polymerization flask over 1 hour to reduce residual monomer. After the ethyl acetate was removed under vacuum at 55-60°C, an acrylic adhesive II was obtained with a weight average molecular weight Mw of 58,000 g / mol, a PDI of 2.6 by GPC, and a viscosity of 130,000 cps at 60°C by Brookfield.

[0110] Example 4 The PSA properties of compounded adhesives prepared by mixing the acrylic polymer from Example 3 with reactive diluent Natureflex X ESO, tackifier R86, and cationic photoinitiator OmniCat 320 are shown in Table 2. All adhesive films were 1 mil thick and were coated directly onto 2 mil PET and irradiated with 40 mJ / cm using a Fusion H bulb. 2The adhesive was cured with 1000 psi UVC and tested for peel, loop tack, and shear on stainless steel panels. Without the addition of epoxidized soybean oil, the adhesive film had no cohesive strength and sheared less than 0.1 hours at 4.4 psi. The addition of epoxidized soybean oil provided high shear strength and reduced peel and tack. The addition of ESO diluent reduced the adhesive viscosity to 50,000-80,000 cps at 30°C, allowing the UV-cured adhesive film to be coated at room temperature.

[0111] [Table 2]

[0112] Example 5 With the appropriate cationic photoinitiator, UV-curable adhesives can also be cured with LED 365 nm lamps, as shown in Table 3. All adhesive films were 1 mil thick and coated directly onto 2 mil PET, with LED 365 nm, dose 600 mJ / cm. 2 The adhesives were cured at 300°C and shear tested on stainless steel panels. OmniCat 320 alone was not sufficiently reactive with LED 365 nm. The adhesive containing photoinitiator NSC-121 (manufactured according to US Patent No. 7,230,122) showed the highest cohesive strength at 27 hours at a shear force of 4.4 psi value. In addition, the adhesives made with NSC-121 also had good compatibility with the acrylic polymer of Example 3, and all the resulting adhesive films were transparent, whereas the films using OmniCat 320 were cloudy. In addition, NSC-121 was thermally stable even below 60°C. Although the acrylic polymer obtained from Example 3 had a viscosity of about 130,000 cps at 60°C, the addition of reactive diluent ESO allowed the adhesive coating temperature to be reduced to below 60°C.

[0113] [Table 3]

Claims

1. A. 10-95% by weight of an acrylic polymer having at least one terminal or pendant reactive functional group selected from the group consisting of cycloaliphatic epoxides, vinyl ethers, oxiranes, oxetanes, and mixtures thereof; B. 4 to 90 wt. % of a reactive diluent essentially free of mono- or multi-(meth)acrylates; and C. 0.01 to 5 wt. % of a cationic photoinitiator; and the total weight of the ultraviolet-curable pressure-sensitive adhesive is 100% by weight.

2. The acrylic polymer is: (i) a first monomer having a reactive functional group selected from a cycloaliphatic epoxide, a vinyl ether, an oxirane, an oxetane, or a mixture thereof; and (ii) Formula CH 2 =CH(R 1 ) (COOR 2 ) an acrylic monomer consisting of an acrylic acid or methacrylic acid derivative of (In the formula, R 1 is H or CH 3 and R 2 is C 1-24 (It is an alkyl chain) Prepared from 2. The ultraviolet-curable pressure-sensitive adhesive of claim 1, wherein the first monomer (i) is present in an amount of from about 0.001 to about 10 g per 100 g of the acrylic polymer (ii).

3. 3. The UV-curable pressure-sensitive adhesive of claim 2, wherein the acrylic polymer has (A) a Tg less than 0° C., and (B) a weight average molecular weight (Mw) of from about 1,000 to about 1,000,000 g / mol.

4. The first monomer (i) has the following formula: 【Chemistry 1】 (In the formula, R 1 is O, S, C=O, or a linear, branched, or cyclic alkylene, oxyalkylene, or arylene; R 2 R is a linear, branched or cyclic alkyl or alkoxy, aryl, H, halogen, C=O, or a covalently fused alicyclic ring. 1 is part of R 3 (CH 2 ) n where n is 0 to 3; X is an acrylate or methacrylate or contains a -W-Y group; W is O, S, amide, carbonate, urethane, urea, siloxane, or combinations thereof; Y is -R 4 -C(R 5 ) = CH 2 and R 4 is a linear or branched chain C 2-10 Alkylene, C 2-10 oxyalkylene, C=O, or arylene or a derivative thereof; R 5 is H or CH 3 (It is) 3. The ultraviolet-curable pressure-sensitive adhesive of claim 2, which is a cycloaliphatic epoxide having the formula:

5. The alicyclic epoxide has the formula: 【Chemistry 2】 (In the formula, R 2 is H or CH 3 (It is) 【Chemistry 3】 【Chemistry 4】 【Chemistry 5】 【Chemistry 6】 【Chemistry 7】 (Wherein, R is H or CH 3 (It is) 【Chemistry 8】 (In the formula, R 1 is H or CH 3 (It is) 5. The ultraviolet-curable pressure-sensitive adhesive according to claim 4, which is a mixture thereof.

6. 2. The ultraviolet-curable pressure-sensitive adhesive of claim 1, wherein the reactive diluent is a polymer, oligomer, or macromer that contains at least one terminal or pendant reactive functional group selected from cycloaliphatic epoxides, oxiranes, oxetanes, vinyl ethers, or mixtures thereof.

7. 7. The ultraviolet-curable pressure-sensitive adhesive of claim 6, wherein the reactive diluent has a weight average molecular weight of about 100 to about 500,000 g / mole.

8. 8. The ultraviolet-curable pressure sensitive adhesive of claim 7, wherein the reactive diluent is an epoxy-functionalized soybean oil, an epoxy-functionalized polybutadiene, an epoxy-functionalized polyurethane, an epoxy-functionalized polysiloxane, an epoxy-functionalized polyisobutylene, an epoxy-difunctionalized bisphenol A epoxy resin, an epoxy-difunctionalized bisphenol F epoxy resin, an epoxy-functionalized polyacrylate, an epoxy-functionalized polyethylene glycol, an epoxy-functionalized polypropylene glycol, an epoxy-functionalized polyether, or a mixture thereof.

9. 9. The ultraviolet curable pressure sensitive adhesive of claim 8, wherein the reactive diluent is an epoxy functionalized soybean oil, an epoxy functionalized polybutadiene, an epoxy difunctionalized bisphenol A epoxy resin, an epoxy difunctionalized bisphenol F epoxy resin, or a mixture thereof.

10. 2. The ultraviolet-curable pressure-sensitive adhesive of claim 1, wherein the cationic photoinitiator is a sulfonium salt or an iodonium salt.

11. The cationic photoinitiator has the following structure: 【Chemistry 9】 (Wherein, R is C 3 H 7 , C 12 H 25 and W is S, SO, SO 2 or CO) The ultraviolet-curable pressure-sensitive adhesive of claim 10 .

12. The cationic photoinitiator comprises: 【Chemistry 10】 (In the formula, R 1 and R 2 are independently H, CH 3 , C 2 H 5 , C 3 H 7 , C 12 H 25 , O.C.H. 3 , O.C. 2 H 5 , O.C. 3 H 7 , or O.C. 12 H 25 (It is) 12. The ultraviolet-curable pressure-sensitive adhesive according to claim 11,

13. 10. The ultraviolet-curable pressure-sensitive adhesive of claim 1, further comprising a tackifier, a thermal stabilizer, or a desiccant.

14. 10. The ultraviolet-curable pressure-sensitive adhesive of claim 1, which is essentially free of organic solvents.

15. (A) an acrylic polymer attached to its backbone with a reactive functional group selected from cycloaliphatic epoxides, oxiranes, oxetanes, vinyl ethers, or mixtures thereof; (B) a reactive diluent having terminal or pendant functional groups selected from cycloaliphatic epoxides, oxiranes, oxetanes, vinyl ethers, or mixtures thereof; and (C) a cationic photoinitiator; An ultraviolet-curable pressure-sensitive adhesive having a matrix comprising: An ultraviolet-curable pressure-sensitive adhesive, wherein the matrix is ​​essentially free of mono- or multi-(meth)acrylate groups.

16. 13. An article of manufacture comprising the ultraviolet-curable pressure-sensitive adhesive of claim 1.

17. 17. The article of manufacture of claim 16 which is a tape, coating, or label.

18. 20. The article of claim 17, further comprising a backing selected from the group consisting of polyester, polypropylene, polyethylene, paper, fabric, polycarbonate, metal, and glass.

19. 2. The cured ultraviolet-curable pressure-sensitive adhesive of claim 1.

Citation Information

Patent Citations

  • Rubber-conductive fiber composite

    JP1994000816A

  • Ultraviolet curing hot-melt type tacky agent composition

    JP1996060127A

  • Expand lattice body for lead-acid battery

    JP1999086876A

  • Photocurable pressure-sensitive adhesive sheet

    JP2003147311A

  • Method for producing acrylic copolymer

    JP2008208149A